Peloruside B, a Potent Antitumor Macrolide from the New Zealand Marine Sponge Mycale hentscheli: Isolation, Structure, Total Synthesis and Bioactivity - Singh, A. Jonathan (2010)
Peloruside B (2), a natural congener of peloruside A (1), was isolated in sub-milligram quantities from the New Zealand marine sponge Mycale hentscheli. Peloruside B promotes microtubule polymerization and arrests cells in the G(2)M phase of mitosis similar to paclitaxel, and its bioactivity was comparable to that of peloruside A. NMR-directed isolation, structure elucidation, structure confirmation by total synthesis and bioactivity of peloruside B are described in this article. The synthesis features Sharpless dihydroxylation, Brown's asymmetric allylboration reaction, reductive aldol coupling, Yamaguchi macrolactonization and selective methylation.